Futsal Defense Strategy Model for Athletes 15-17 Years Old - Akhsin, Silmi; Sukiri; Sulaiman, Iman; Siregar, Nofi Marlina (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to produce a futsal defense strategy training model for athletes 15-17 years old and to test the effectiveness of the futsal defense model for ages 15-17 years. The method used in this research is research and development. Data collection techniques using interviews, tests, and field observations. The results of the product effectiveness test by comparing the two groups; the treatment group using the product development, and the control group using the pretest and posttest designs. The average value of each group based on the test is the effectiveness of the experimental group is higher than the control group. The improvement of the futsal defense system for the age of 15-17 years at the time of the pre-test showed t-count = 13,405, >t-table = 1.69236, df = 34 and p-value = 0.000.00<0.005. Based on the comparison of the test results, the increase in test results for the experimental group increased significantly than the control group. The subjects in this study were athletes of Club futsal in Soppeng Regency aged 15-17 years and AFK Soppeng athletes aged 15-17 years. It is hoped that this research can provide benefits for sports practitioners, especially in futsal sport.